Analisis Faktor – Faktor Yang Mempengaruhi Kepuasan Dan Word Of Mouth Yang Positif Pada Pelanggan Telkom Speedy Di Kota Manado - Ulag, Acid (Universitas Sam Ratulangi, 2014)
Word-of-mouth phenomenon in the last decade can not be avoided by marketers, because its existence can carry a positive or negative image of one brand of product or service. The data analysis in this study uses the PATH analysis using the analysis tool SPSS (Statistical Package for Social Sciences). The test results showed that the Product Quality and Service Quality in the process eliminated the t test because it has a low impact on customer satisfaction. Competitive prices have a dominant influence on Customer Satisfaction. Similarly, the effect of Customer Satisfaction on Word Of Mouth is the value of positive significance. This means that the higher the price is competitive assessment of customer owned, the higher the customer satisfaction of the Speedy and the higher the resulting effect of Word Of Mouth. Keywords: product quality, service quality, customer satisfaction, and word of mouth